2017
DOI: 10.1111/cid.12493
|View full text |Cite
|
Sign up to set email alerts
|

Does osteoporosis influence the marginal peri‐implant bone level in female patients? A cross‐sectional study in a matched collective

Abstract: There is no contraindication to place dental implants in osteoporotic patients. This study implicates to respect the bone level at implant placement and not to place the implant below bone level if possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
(106 reference statements)
1
35
1
2
Order By: Relevance
“…Reason for exclusion Stvrtecky, Kaufman, and Borgetti, (1995) Only 9 patients Marx, Sawatari, Fortin, and Broumand (2005) Only 4 Famili and Zavoral (2015) Only 3 patients with relevant medication intake Nisi et al (2015) Only 9 patients with MRONJ associated with implants Rugani, Kirnbauer, Acham, Truschnegg, and Jakse (2015) Single case report Matsuo et al (2016) Only 6 patients Gurgel et al (2017) Patients with BP and/or HRT intake not reported separately Wagner et al (2017) Only 5 patients with BP intake…”
Section: Appendix 1 Information Sources and Literature Searchmentioning
confidence: 99%
“…Reason for exclusion Stvrtecky, Kaufman, and Borgetti, (1995) Only 9 patients Marx, Sawatari, Fortin, and Broumand (2005) Only 4 Famili and Zavoral (2015) Only 3 patients with relevant medication intake Nisi et al (2015) Only 9 patients with MRONJ associated with implants Rugani, Kirnbauer, Acham, Truschnegg, and Jakse (2015) Single case report Matsuo et al (2016) Only 6 patients Gurgel et al (2017) Patients with BP and/or HRT intake not reported separately Wagner et al (2017) Only 5 patients with BP intake…”
Section: Appendix 1 Information Sources and Literature Searchmentioning
confidence: 99%
“…A more common disease affecting bones is osteoporosis. Generally speaking, there is no contraindication to apply dental implants in osteoporosis patients; the implant survival rate is comparable to that observed in healthy controls (Alqutaibi & Radi, 2016;Temmerman, Rasmusson, Kübler, Thor, & Quirynen, 2017;Wagner et al, 2017).…”
Section: Bone Diseasesmentioning
confidence: 71%
“…A more common disease affecting bones is osteoporosis. Generally speaking, there is no contraindication to apply dental implants in osteoporosis patients; the implant survival rate is comparable to that observed in healthy controls (Alqutaibi & Radi, ; Temmerman, Rasmusson, Kübler, Thor, & Quirynen, ; Wagner et al., ). However, the rate of peri‐implant bone loss might be slightly higher in osteoporosis patients, but this observation is in need of long‐term follow‐up.…”
Section: Bone Diseasesmentioning
confidence: 75%
“…In diabetic patients failures started from the first few months and continued over the following 10 years; in smokers, most failures occurred within the first year, with very few failing at later time points. 26 Osteoporosis is not contraindication to implant therapy, 15,23,[27][28][29] and some authors have compared osteoporotic bone to the proposed model of bone type four. 15,29 In addition, osteoporotic patients treated with oral bisphosphonates which is an antiresorptive medication have low risk of developing osteonecrosis, 15,29 but there is a high risk of osteonecrosis in patients receiving intravenous bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%